Identification of Critical Factors and Their Interrelationships to Design Agile Supply Chain : Special Focus to Oil and Gas Industries - Piya, Surjan; Shamsuzzoha, Ahm; Khadem, Mohammad; Al-Hina, Nasr (Springer, 2020)
Purpose – This research attempted to identify the most critical factors and their inter-relationships to ensure designing agile supply chain, especially in oil and gas industry. This factors identification process is performed through developing a conceptual framework and the use of Interpretive Structural Modelling (ISM) tool. Design/methodology/approach – This study is conducted through an extensive literature review and questionnaires survey to identify and refine the critical factors that ensure the agile supply chain in oil and gas industry. In addition, several brainstorming sessions with the experts in the field of oil and gas industries were organized with the objective to interpret the contextual inter-relationships between the identified factors. The outcomes from the literature reviews, interview questions and experts’ opinions were used to develop a diagraph and MICMAC analysis to know the drivers of agility in supply chain. Findings –From this study, 34 enablers and 12 factors were identified, which are responsible to ensure agile supply chain in oil and gas industry. Out of these identified factors, top management commitment, strategic alignment, competency of management and integration of information and systems technology are found to be the critical drivers of supply chain agility. On the other hand, government regulations, transportation and logistics flexibility and production planning and control falls under the category of dependent factors. Originality/value – The identified factors and their interrelationships can be a valuable aid to ensure and measure the agility in supply chain, especially in oil and gas industry. These identified factors and their defined consequences will help managers and concerned authorities in oil and gas industry to take better decision to improve the agility level of their supply chain.
Keywords: oil and gas industries; total interpretive structural modeling; supply chains; agility; fi=Tuotantotalous|en=Industrial Management|